2016
DOI: 10.1016/j.fertnstert.2016.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of fertility treatment and reproductive choices by lesbian couples

Abstract: Lesbian couples may improve their likelihood of a live birth if both partners attempt conception. Further studies are needed to understand why one-fifth of patients did not pursue treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 5 publications
2
22
1
Order By: Relevance
“…Second, we compared our IVF/ICSI results with those reported in previous studies. 2,9,10 With regard to the first ET results, we report a clinical pregnancy rate of 40.0%, somewhat higher than the 34.4% reported by Fiske and Weston 2 (further pregnancy outcomes were not reported). Similarly, we obtained a live birth rate of 29.8%, close to the 26.2% reported by Nordqvist et al 9 When considering cumulative live birth rates, we obtained 43.4% in the IVF/ICSI group, after an average of 1.4 -0.7 ETs.…”
Section: Discussioncontrasting
confidence: 65%
“…Second, we compared our IVF/ICSI results with those reported in previous studies. 2,9,10 With regard to the first ET results, we report a clinical pregnancy rate of 40.0%, somewhat higher than the 34.4% reported by Fiske and Weston 2 (further pregnancy outcomes were not reported). Similarly, we obtained a live birth rate of 29.8%, close to the 26.2% reported by Nordqvist et al 9 When considering cumulative live birth rates, we obtained 43.4% in the IVF/ICSI group, after an average of 1.4 -0.7 ETs.…”
Section: Discussioncontrasting
confidence: 65%
“…According to the most recent data, 440,986 U.S. women used donor insemination (DI) in family creation in 2015-2017 (1). Although most insemination recipients are heterosexually coupled and have infertility or a genetically transmitted disease, lesbian-identified women are increasingly using DI to become pregnant (2). The first generation of DI-conceived offspring from lesbian-parent families has now entered adulthood in substantial numbers.…”
mentioning
confidence: 99%
“…A publication by Carpinello et al showed that in 2015, the majority of those utilizing donor intrauterine insemination (DIUI) at a single site were SSFCs, whereas SSFCs made up less than 1% of therapeutic donor insemination users in 1985. 1 Additionally, a single-center study in Australia observed overall trends in reproductive treatment use among single women and SSFCs prior to and following a legislation change, which previously limited reproductive treatment utilization to married heterosexual couples with medical infertility. The same study showed that after the change in legislation, a 102.8% increase in utilization was observed among the single woman population, and a 258.8% increase in reproductive treatment cycles was seen among SSFCs during the same time period.…”
Section: Same-sex Female Couples: Biological Obstaclesmentioning
confidence: 99%
“…In the literature, co-IVF has also been referred to as "ROPA" (reception of oocytes from partner), shared conception, shared maternity, or shared parenthood. 1 Co-IVF involves one woman who undergoes ovarian stimulation and vaginal oocyte retrieval, while her partner receives the developed embryo(s) through transfer and carries out the pregnancy. The process of co-IVF is analogous to heterosexual couples who utilize an ovum donor; albeit SSFCs will always require a sperm donor.…”
Section: Same-sex Female Couples: Treatment Strategymentioning
confidence: 99%
See 1 more Smart Citation